The association between perceived stigma and substance use disorder treatment outcomes: a review - Crapanzano KA; Hammarlund R; Ahmad B; Hunsinger N; Kullar R (Dove Medical Press, 2018)
Kathleen A Crapanzano,1 Rebecca Hammarlund,2 Bilal Ahmad,1 Natalie Hunsinger,1 Rumneet Kullar1 1Department of Psychiatry, Louisiana State University Health Sciences Center, Baton Rouge, LA, USA; 2Our Lady of the Lake Division of Academic Affairs, Baton Rouge, LA, USA Abstract: Substance use disorders (SUDs) take a heavy toll on those who have them and on society more broadly. These disorders are often difficult to treat, and relapse is common. Perhaps, because of these factors, these disorders are highly stigmatized worldwide. The purpose of this study is to examine empirical work intended to determine the impact of perceived social stigma and self-stigma on the process of recovering from SUDs with the assistance of formal treatment services. Qualitative studies confirmed that stigma experiences are common among those with these disorders and that these experiences can negatively impact feelings and beliefs about treatment. One quantitative study provided good statistical support for a direct effect of stigma on outcomes, but this was contradicted by other longitudinal data. In general, quantitative articles suggested an indirect effect of stigma on treatment outcomes, via negative emotions and cognitive mechanisms such as feelings of self-efficacy. However, it was notable that there was little consistency in the literature as to definitions and measurement of the constructs of recovery, perceived social stigma, and self-stigma. Future work should focus on bringing clarity, and validated measures, to this problem in order to better determine the nature of these relationships. Keywords: self-stigma, perceived social stigma, substance use disorders, treatment outcomes